Zasebni vodnjaki in vrtine na območju Ljubljane - Kladnik, Drago (Georitem, 2007)
The book includes water protection areas near the pumping stations of drinkable water on Ljubljansko polje, consequently in the City municipality of Ljubljana and in the water protection area of the water plant Brest in the neighbouring municipality of Ig. The area of Ljubljansko barje was also included in the study.Water wells have, besides the basic function of preserving water, also an aesthetic and symbolic meaning. Many fountains in public and private use are true works of art, but that wasn't the main interest of our study. We concentrated mostly on private water wells and bores, which are not registered and therefore not supervised.